The complexity of the patient with chronic illness: What is the best way to organize care to meet their needs? (Portuguese Journal of Family Medicine and General Practice, 2007)
This case presentation describes patient with multiple chronic diseases, who is a heavy user of health care services. It reflects the high degree of complexity inherent in chronic diseases, complicated by co-morbidity. The case raises issues related to the approach to chronic diseases (CD) in the National Health Service (NHS). Proposals for the improvement of the organization of health care are presented, in order to address the needs of patients with chronic illness. This includes an analysis of the integration of health care services, of the underlying strategies and benefits of care, the concept of disease management (DM) and its role in the integration and improvement of quality of care for these patients.